Quelques notes sur l’architecture mésopotamienne des IIe et Ier millénaires av. J.-C. : l’ensemble de réception des palais - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
According to general belief, the palace of Adad-Nirari I was the first to create a planimetric typology typical of Neo-Assyrian palaces, i.e. construction based on babanu and bitanu. Yet this palace has strong similarities with the palatial architectural tradition of the Middle Bronze Age, especially as regards the official reception complex. The aim of this article is to show the continuity of palace architecture from the Middle Bronze to the Iron Age.